Problematika Manajemen Pendidikan Islam pada Era Society 5.0: Kajian Literatur Sistematis - Aina Mardlaatillah; Husnul Hotimah; Marsanda Saputri; Farhan Farhan; Ahmad Ridwan (MAN 4 Kota Pekanbaru, 2025)
The era of Society 5.0 demands profound transformation within Islamic Education Management (MPI), particularly in integrating Islamic values with technological advancements such as AI, IoT, and big data. This study employs the Systematic Literature Review (SLR) method to identify and classify key issues faced by MPI in the disruptive digital era. The findings reveal four major problems: non-adaptive leadership and digital culture, insufficiently innovative curricula that have yet to fully integrate 21st-century competencies, limited infrastructure and persistent digital divides across regions, and low human resource competence in digital literacy and pedagogy. These results highlight the need for adaptive strategies, including strengthening digital leadership, updating technology-based curricula, expanding equitable access to digital infrastructure, and enhancing human resource capacity through continuous training. This research provides an important contribution to mapping managerial challenges and offers strategic recommendations for realizing Islamic education governance that is relevant, innovative, and competitive in the Society 5.0 era.